Bioenergetic transcriptomic responses of European flounder (Platichthys flesus) populations in contrasted environments: impacts of pollution and global warming - E. Borcier; G. Charrier; A. Amérand; M. Théron; V. Loizeau; N. Pédron; J. Laroche (MDPI AG, 2016)
Not available